Screening and genetic counselling for relatives of patients with breast cancer in a family cancer clinic. - Houlston, R S (1992)
Family history is the major risk factor in the aetiology of breast cancer. Breast screening is currently available to women from the age of 50 to 64 through the National Breast Screening Programme. There is, however, an equivalent risk of developing breast cancer below 50 for first degree relatives of women diagnosed with breast cancer premenopausally. We have estimated the risk of breast cancer for relatives of women affected at different ages and used these to establish a family cancer clinic offering breast screening based on individual risk. In three years we have seen 851 patients. Compliance for annual radiology was in excess of 83% over this period and of five cancers detected one had a lump at presentation, two developed interval breast lumps, and two were asymptomatic.